Can state-owned equity participation promote private enterprises’ fulfilment of social responsibilities?——based on the perspective of rural revitalisation participation* - Liguang Zhang; Ruoyi Yang; Yunxiang Liao; Yunchen Wang (China Journal of Accounting Studies)
If the countryside prospers, the country prospers. By taking the private A-share listed companies in Shanghai and Shenzhen as research samples, we examine how state-owned equity participation affects private enterprises’ fulfilment of social responsibilities and its consequences. We find that state-owned equity participation significantly increases the probability and scale of investment by private enterprises in rural revitalisation, and this effect is primarily observed in samples with greater financial pressure, lower farmer incomes, higher media attention and lower levels of market competition. Mechanism analysis suggests that state-owned equity participation influences private enterprises’ participation in rural revitalisation primarily through alleviating financing constraints, affecting attention allocation and increasing policy-related burdens. In terms of economic consequences, participation in rural revitalisation driven by state-owned equity participation is beneficial for improving private enterprise performance. Our research not only enriches the research on corporate social responsibility fulfilment from the perspective of state-owned equity participation but also provides a policy basis for the government to deepen the reform of mixed ownership.